Modification of the olfactory sensory characteristics of Chardonnay wine through the increase in sotolon concentration. (March 2017) - Caillé, Soline; Salmon, Jean-Michel; Bouvier, Nicolas; Roland, Aurélie; Samson, Alain
Highlights: A Chardonnay wine was spiked with increasing amounts of titrated sotolon. A sensory panel described the olfactory sensations associated. Several new olfactory attributes were generated by the panel. The attributes were perceived as different according to the sotolon concentration range studied. Abstract: Among lactones formed during the oxidative maturation of wines, sotolon (3-hydroxy-4, 5-dimethyl-2[5H] furanone), with an odor reminiscent of nut and curry, and its low perception threshold, is known to have a significant impact on the aroma. Although recent research work has designated sotolon as one of the contributors to the specific Chardonnay olfactory space, sotolon is still mainly described for its sole nut and curry olfactory characteristics. The present work is aiming at evaluating the potential involvement of sotolon in small concentrations as a contributor to the complex sensory characteristics of Chardonnay wine. For this purpose, a Chardonnay wine was spiked with increasing amounts of a titrated sotolon solution, resulting in a concentration ranging from 0 to 60 μg L −1 . A sensory panel was then asked to describe the olfactory sensations associated with these incremental changes. The study demonstrated that several new olfactory attributes were generated by the panel in response to sotolon addition, and that these attributes were significantly different depending on the sotolon concentration range studied.